Effectiveness of Motivational Interviewing on Self-Management of Type 2 Diabetes Mellitus Patients: A Systematic Review - Lestari, Siska Puji; Wihastuti, Titin Andri; Sartika Lestari Ismail, Dina Dewi (Jurnal Kedokteran Brawijaya, 2021)
Diabetes mellitus is a health problem that will affect the health status of patients. Motivational interviewing a counseling technique focusing on clients and it is designed for helping individuals explore and accomplish ambivalence in behavior. This systematic review aimed at describing effectiveness motivationaI interviewing on self-management of diabetes mellitus type 2 patients. There are 1359 articles of 526 ScienceDirect articles, 422 ProQuest, 290 PubMed, and 121 Ebsco articles. The systematic review method began by identifying 20 articles from four electronic databases for previous studies that were published during 2011-2021. The results of the systematic review obtained that motivational interviewing can provide improved self-management and control blood glucose DM type 2 patients. The conclusion motivational interviewing can affect the patient's self-management especially on blood glucose profile, dietary compliance, quality of life, self-efficacy, HbA1c levels of DM type 2 patients.